Development Of Risk-Based Work Breakdown Structure (WBS) Standards For Integrated Design And Construction Phase On Design-Build Method Of Architectural Works Of High-Rise Building To Improve Construction Safety Performance - Andina Ganesdhi, Gabby; Latief, Yusuf; Budi Nugroho, Danang (Publisher Cv. Inara, 2023)
Design-build methods are one of the options in carrying out the construction of high-rise buildings with a high level of uncertainty from design phase to construction, which also affects the safety performance of the project itself. Therefore, a prevention standard for a high-risk event is needed based on project activities. This research was prepared using a descriptive qualitative method with expert validation process through Delphi method and completed with a questionnaire survey to conduct a risk assessment. The output in this research is a development of risk-based standard work breakdown structure for architectural work, which generated from 39 high level risk. Based on the results of the mapping of preventive and corrective actions at high-level risks, 5 types of WBS development can be carried out at levels 3 to 6 of the WBS to prevent and minimize the impact of risk so that safety performance could be improved. The novelty in this research lies in the form of design-build project delivery activities which has not been widely discussed in previous work breakdown structure research and risk identification based on the activities listed on the WBS.